(I)∵数列{an}的前n项和Sn=2n2+2n,
∴a1=S1=2+2=4,
an=Sn-Sn-1=(2n2+2n)-[2(n-1)2+2(n-1)]=4n,
当n=1时,4n=4=a1,
∴an=4n.
∵数列{bn}的前n项和Tn=2-bn,
∴当n=1时,T1=b1=2-b1,解得b1=1.
当n>1时,Tn=2-bn,Tn-1=2-bn-1,
∴Tn-Tn-1=bn=bn-1-bn,∴2bn=bn-1,
∴=,
∴数列{bn}是以首项为1,公比为的等比数列,
∴bn=()n-1,n∈N*.
(II)∵cn==n•()n-1,
∴数列{cn}的前n和:
Rn=c1+c2+c3+…+cn
=1•()0+2×()1+3×()2+…+(n-1)•()n-2+n•()n-1,①
∴Rn =1•()1+2×()2+3×()3+…+(n-1)•()n-1+n•()n,②
①-②,得Rn=1++()2+()3+…+()n-1-n•()n
Rn=-n•()n
=2-()n+1-n•()n,
∴Rn=4-2(n+2)()n<4;
( III)∵cn=an+(-1)nlog2bn
=4n+(-1)nlog2()n-1
=4n+(-1)n(1-n),
∴数列{cn}的前2n和
R2n=[4×1+(-1)1(1-1)]+[4×2+(-1)2(1-2)]+[4×3+(-1)3(1-3)]+…+[4×2n+(-1)2n(1-2n)]
=4(1+2+3+…+2n)+[0-1+2-3+…+(2n-2)-(2n-1)]
=4×-n
=8n2+3n.
∴R2n=8n2+3n.